Oral lichen planus and hepatitis C virus - Al Robaee, Ahmad A. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Lichen planus is an inflammatory, mucocutaneous disease that in addition to the skin involves oral mucosa in about 60-70 % of cases. In recent years, several reports have supposed a relationship between oral lichen planus (OLP) and chronic liver disease, especially hepatitis C (HCV). Here we present an extensive review of the literature in English that examines the association between HCV and OLP.
Keywords: glivične bolezni; Hepatitis C; Hepatitis C-Like Viruses; Hepatitis, C-podobni virusi; Lichen Planus; Lihen planus; ustna sluznica